High rate biofiltration - Bedard, P. (Cranfield University, School of Water Sciences, 1999)
High rate biofiltration is a process which has gained popularity in recent years as effluent discharge consents become ever more stringent and the available land to construct new facilities becomes more scarce. This paper discusses the developments in the Biofor® process, which has allowed the previous design limiting parameters to be increased. Significant improvements in technology combined with a better understanding of the biofiltration mechanism have allowed a new generation of Biofor® plants to be constructed. This is due to a significant program of development work focussing on increasing the water velocity through the filter, to allow an increased applied loading rate without impairing filter performance.
Keywords: Biological Aerated Filter; carbon removal; nitrification; denitrification; upflow filter; land availability; applied load; water velocity